What's in a Typeface? Evidence of the Existence of Print Personalities in Arabic - Jordan, Timothy R.; AlShamsi, Alya S.; Yekani, Hajar A. K.; AlJassmi, Maryam; Al Dosari, Nada; Hermena, Ehab W.; Sheen, Mercedes (Frontiers in Psychology, 2017)
Previous research suggests that different typefaces can be perceived as having distinct personality characteristics (such as strength, elegance, friendliness, romance, and humour) and that these “print personalities” elicit information in the reader that is in addition to the meaning conveyed linguistically by words. However, research in this area has previously been conducted using only English stimuli and so it may be that typefaces in English, and other languages using the Latinate alphabet, lend themselves unusually well to eliciting perception of print personalities, and the phenomenon is not a language universal. But not all written languages are Latinate languages, and one language that is especially visually distinct is Arabic. In particular, apart from being read from right to left, Arabic is formed in a cursive script in which the visual appearance of letters contrasts strongly with those used for Latinate languages. In addition, spaces between letters seldom exist in Arabic and the visual appearance of even the same letters can vary considerably within the same typeface depending on their contextual location within a word. Accordingly, the purpose of the present study was to investigate whether, like English, different Arabic typefaces inspire the attribution of print personalities. Eleven different typefaces were presented in Arabic sentences to skilled readers of Arabic and participants rated each typeface according to 20 different personality characteristics. The results showed that each typeface produced a different pattern of ratings of personality characteristics and suggest that, like English, Arabic typefaces are perceived as having distinct print personalities. Some of the implications of these results for the processes involved in reading are discussed.